HIV-1 envelope replication and α4β7 utilization among newly infected subjects and their corresponding heterosexual partners - Pena-Cruz, Victor; Etemad, Behzad; Chatziandreou, Nikolaos; Nyein, Phyu Hninn; Stock, Shannon; Reynolds, Steven J; Laeyendecker, Oliver; Gray, Ronald H; Serwadda, David; Lee, Sandra J; Quinn, Thomas C; Sagar, Manish (Retrovirology, 2013)
Previous studies suggest that active selection limits the number of HIV-1 variants acquired by a newly infected individual from the diverse variants circulating in the transmitting partner. We compared HIV-1 envelopes from 9 newly infected subjects and their linked transmitting partner to explore potential mechanisms for selection. Recipient virus envelopes had significant genotypic differences compared to those present in the transmitting partner. Recombinant viruses incorporating pools of recipient and transmitter envelopes showed no significant difference in their sensitivity to receptor and fusion inhibitors, suggesting they had relatively similar entry capacity in the presence of low CD4 and CCR5 levels. Aggregate results in primary cells from up to 4 different blood or skin donors showed that viruses with envelopes from the transmitting partner as compared to recipient envelopes replicated more efficiently in CD4+ T cells, monocyte derived dendritic cell (MDDC) - CD4+ T cell co-cultures, Langerhans cells (LCs) - CD4+ T cell co-cultures and CD4+ T cells expressing high levels of the gut homing receptor, α4β7, and demonstrated greater binding to α4β7 high / CD8+ T cells. These transmitter versus recipient envelope virus phenotypic differences, however, were not always consistent among the primary cells from all the different blood or skin donation volunteers. Although genotypically unique variants are present in newly infected individuals compared to the diverse swarm circulating in the chronically infected transmitting partner, replication in potential early target cells and receptor utilization either do not completely dictate this genetic selection, or these potential transmission phenotypes are lost very soon after HIV-1 acquisition.